Wrinkle structures formed by formulating UV-crosslinkable liquid prepolymers. (2nd September 2016) - Park, Seung Koo; Kwark, Young-Je; Nam, Saekwang; Park, Suntak; Park, Bongje; Yun, Sungryul; Moon, Jaehyun; Lee, Jeong-Ik; Yu, Byounggon; Kyung, Ki-Uk
Abstract: Artificial wrinkles have recently been in the spotlight due to their potential use in high-tech applications. A spontaneously wrinkled film can be fabricated from UV-crosslinkable liquid prepolymers. Here, we controlled the wrinkle formation by simply formulating two UV-crosslinkable liquid prepolymers, tetraethylene glycol bis(4-ethenyl-2, 3, 5, 6-tetrafluorophenyl) ether (TEGDSt) and tetraethylene glycol diacrylate (TEGDA). The wrinkles were formed from the TEGDSt/TEGDA formulated prepolymer layers containing up to 30 wt% of TEGDA. The wrinkle formation depended upon the rate of photo-crosslinking reaction of the formulated prepolymers. The first order apparent rate constant, k app, was between ca. 5.7 × 10 −3 and 12.2 × 10 −3 s −1 for the wrinkle formation. The wrinkle structures were modulated within the k app mainly due to variation in the extent of shrinkage of the formulated prepolymer layers with the content of TEGDA. Graphical abstract: Highlights: Wrinkle structures of UV-cured films were formed by formulating liquid prepolymers. The wrinkle formation depended on the formulation ratio between the prepolymers. The rate of photo-crosslinking reaction was within a specific range for the wrinkle formation. The wrinkle modulation came mainly from variation in the extent of shrinkage.